Design and synthesis of selenazole-substituted ritonavir analogs. Issue 14 (1st August 2018) - Qiao, Junfei; Zhao, Chuanfang; Liu, Jun; Du, Yuguo
Graphical abstract: Two new ritonavir analogs were designed and synthesized taking advantages of one-pot cascade condensation of β-azido diselenide and alkyl acids. The prepared compounds exhibited good anti-HIV-1 activities as well as the positive SI values. Highlights: New method to make selenazole from β-azido diselenide and alkyl acids in one-pot. Two new selenazole-containing ritonavir analogs were designed and synthesized. The designed compounds exhibited promising anti-HIV-1 activities and SI values. Abstract: With the help of Surflex-Dock calculation, two ritonavir analogs in which one thioazole unit was replaced by selenazole have been designed and synthesized. The key selenazole structure was constructed from β-azido diselenide through a cascade diselenide cleavage/selenocarbonylation/Staudinger reduction/aza-Wittig reaction and a following MnO2 oxidation. The accordingly prepared compounds exhibited good anti-HIV-1 (IIIB) activities comparable to that of the original ritonavir, as well as the positive SI values.